ANALYSIS OF INFLATION EFFECT AND INTEREST RATES FOR CURRENCY EXCHANGE RATE IN THAILAND - Perwiro, Herjuno (Journal Economics & Business Atmajaya Indonesia, 2019)
This study attempted to examine the effect of inflation and interest rates on exchange rates in a country. Thailand was the object of this study. This study made use of secondary data collected from the central bank of Thailand. The data collected in this study focused on inflation and used CPI Headline, interest rate and Baht/USD exchange rate between 1979 and 2019 as parameters. To generate results and draw conclusion, hypothesis was tested by running linear regression in R Studio. Analysis results demonstrated influences of inflation and interest rate on Baht/USD exchange rate.